Convergence Theorems on Asymptotically Pseudocontractive Mappings in the Intermediate Sense. (30th March 2010) - Qin, Xiaolong; Cho, Sun Young; Kim, Jong Kyu
Abstract : A new nonlinear mapping is introduced. The convergence of Ishikawa iterative processes for the class of asymptotically pseudocontractive mappings in the intermediate sense is studied. Weak convergence theorems are established. A strong convergence theorem is also established without any compact assumption by considering the so-called hybrid projection methods.